Enhancing Financial Literacy and Economic Resilience: A Community-Based Education Initiative for Fish Farmers and Local Enterprises in Tarakan, Indonesia - Suryaningsih, Suryaningsih; Rukisah, Rukisah; Satriani, Gloria Ika; Fajriansyah, Andi; Sanjaya, M. Feldi; Trisnawan, M. Ridho (International Journal of Community Service (IJCS), 2025)
This community service activity aims to enhance community financial literacy through simple financial education for the Fish Farmers Group (Pokdakan) “Raja Ikan” and the Community Group (Pokmas) “Antara Lestari” in Kampung Empat, Tarakan City. The program was carried out as an empowerment initiative for coastal communities to develop basic financial management skills for both household and business purposes. The activity employed a participatory and dialogical approach involving material presentation, interactive discussions, and real-life case analyses relevant to the participants’ socio-economic context. The materials focused on separating personal and business finances, understanding cash flow, managing capital, and applying simple bookkeeping practices. The results indicated an improvement in participants’ understanding of fundamental financial management concepts and increased awareness of the importance of financial record-keeping in daily business activities. This activity served as an initial step toward fostering sound financial behavior and promoting economic independence among coastal communities in Tarakan City.